Disclosures on Risk Based Capital (Basel-III): A Comparative Analysis of Commercial Banks in Bangladesh - Lamina Binta Jahan (Academic Journal on Business Administration, Innovation & Sustainability, 2021)
As part of a consistent journey to enhance the loss absorption capacity and resilience of the banks through increasing the capital and improving the quality thereof, Bangladesh Bank has given directions to banks to implement Basel III from January 01, 2015 in phases and fully by January 01, 2019.Basel III reforms are the response of Basel Committee on Banking Supervision (BCBS) to improve the banking sector’s ability to absorb shocks arising from financial and economic stress, whatever the source, thus reducing the risk of spillover from the financial sector to the real economy.The aim of this study is to find out market disclosure on risk based capital with comparison among state owned banks, private banks & foreign banks from 2015-2017. Secondary data have been used to conduct the study. Thesedisclosures requirements should be more applicable and Bangladesh bank will also assist the commercial banks to follow the instructions more efficiently for smooth implementation of Basel III framework in the banking sector of Bangladesh. Keywords: , , , ,.